2014
DOI: 10.1093/neuonc/nou148
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of sunitinib for recurrent and progressive atypical and anaplastic meningioma

Abstract: Sunitinib is active in recurrent atypical/malignant meningioma patients. A randomized trial should be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
143
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(152 citation statements)
references
References 34 publications
3
143
1
5
Order By: Relevance
“…Sunitinib has a dose‐dependent effect on QTc prolongation. Subsequent trials with sunitinib with cardiac safety monitoring have reported an average incidence of QTc prolongation of any degree of 8.5% and a QTc >500 ms of 1.7% without any arrhythmia 15, 23, 28, 37…”
Section: Resultsmentioning
confidence: 99%
“…Sunitinib has a dose‐dependent effect on QTc prolongation. Subsequent trials with sunitinib with cardiac safety monitoring have reported an average incidence of QTc prolongation of any degree of 8.5% and a QTc >500 ms of 1.7% without any arrhythmia 15, 23, 28, 37…”
Section: Resultsmentioning
confidence: 99%
“…65 Sunitinib, an oral RTK inhibitor against VEGFR, PDGFR, and KIT, achieved a 6-month PFS of 42% in Grade II and III meningiomas. 39 Agents against VEGFR and VEGF, including RTK inhibitors and bevacizumab, respectively, have demonstrated 6-month PFS rates of 42%-64% against AM and MM. 39,65 This relative success must be tempered, however, by the high rate of side effects and the low median overall survival (OS) with chemotherapy for these surgery-and radiation-refractory Grade II and III meningiomas, at approximately 24 months.…”
Section: Chemotherapymentioning
confidence: 99%
“…39 Agents against VEGFR and VEGF, including RTK inhibitors and bevacizumab, respectively, have demonstrated 6-month PFS rates of 42%-64% against AM and MM. 39,65 This relative success must be tempered, however, by the high rate of side effects and the low median overall survival (OS) with chemotherapy for these surgery-and radiation-refractory Grade II and III meningiomas, at approximately 24 months. 39,55,56,65 Chemotherapy for AMs shows promise but should only be considered for select refractory tumors as salvage therapy.…”
Section: Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Bevacizumab oder Sunitinib [30,31]. Therapieversuche mit dem Somatostatin-RezeptorAgonisten Octreotid waren weitgehend erfolglos [32].…”
Section: In Diesem Beitrag Werden Therapiestandards Und Neue Entwicklunclassified